ANALISIS ENERGI INDONESIA : APLIKASI LEAP - , EKA IRAWAN, Tri Widodo, Prof. M.Ec.Dev., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper aims to analyze the energy Indonesia from 2010 to 2030, energy consumption in the count of four sectors